السيادة المخية النصفية والتماسك الأجتماعي وعلاقتهما ببعض المهارات الهجومية المركبة للاعبات كرة السلة - محمد, ياسين عمر; هيلير, سارا مايكل; رؤوف, رزكار محمد (Sulaimani Journal for Humanities, 2018)
The aim of the research: - Recognizing the level of the brain electrical activity and social cohesion with some complex offensive skills for Serwane new Women basketball players. - Recognizing the level of the brain electrical activity and some complex offensive basketball 333 مجلة )زانکۆی سلێمانی( القسم )B )للعلوم االنسانیة – العدد )75( – تموز 8102 skills for the sample of the study. - Recognizing the type of relationship between social cohesion and some complex offensive basketball skills for the sample of the study. The researcher used the descriptive method with the associative manner to suit with the nature of the study. The research has been applied on a sample of the Serwane nwe girls basketball players (16) players. The researcher used some tools and devices for collecting data then variables and metrics were designated plus the skills tests. After conducting the exploratory experiments, the scientific bases of the scales and the skills tests were found. He translated both scales in to Kurdish then worked on the final experiment. The researchers used some statistical means like (arithmetic means, standard deviation, median and the Ka2 value) for data processing. The researchers came out with next conclusions: - The samples of the study have had different and certain degree of learning and thinking patterns with a certain degree of social cohesion and complex offensive skills. - A correlation relationship is not significant were found between brain electrical activity (learning and thinking patterns) and all of the basketball skill tests for the Serwnae nwe girls basketball players. - A correlation relationship is not significant were found between social cohesion and (receiving + overhead pass + dribbling + layups) for the sample of the study while a significant relationship were found for receiving, dribbling and chest pass. - A correlation relationship is significant between social cohesion and complex offensive basketball skills (receiving + dribbling + layups).